FORSTERITIC OLIVINE: EFFECT OF CRYSTALLOGRAPHIC DIRECTION ON DISSOLUTION KINETICS - Awad A.; Koster van Groos A.F.; Guggenheim S. (My University, 2000)
Directional dissolution along the three crystallographic axes of gem-quality olivine (Fo91), San Carlos, Arizona was studied at pH 1 and pH 2 at 23, 50, 70, and 90°C and 1 atm. The rate constant of dissolution for olivine at pH 1 and 70°C down the a-, b-, and c-axis (based on space group Pbnm) is 2.7 x 10-4, 5.6 x 10-3, and 8.1 x 10-4 mm/h, respectively. At pH 2 and 70°C the dissolution rates are 1.3 x 10-4, 2.1 x 10-3, and 4.3 x 10-4 mm/h, respectively. At 50°C and 90°C, these rates are ~0.2 and 5 times the rates at 70°C. The much higher dissolution rate in the direction of the b-axis is attributed to preferential protonation of the oxygen atoms around the M(1) site, which would result in a higher dissolution rate of the SiO2-M(1) network. The activation energy of dissolution Eadis in the direction down the a-, b-, and c-axis is 114.5 +/- 23 kJ/mol, 69.9 +/- 8 kJ/mol, and 72.9 +/- 15 kJ/mol, respectively. Because of differences in the directional Eadis, dissolution in the direction down the a-axis will become dominant at temperatures above ~140°C. The bulk Eadis, based on the dissolution rate along the crystallographic axes, is 71.5 +/- 12 kJ/mol at the temperature range of the study. Because of the larger Eadis perpendicular to the a-axis, bulk Eadis must increase with temperature. The results indicate that the weathering rate of olivine is more temperature dependent than was considered previously.